ACCOMPLISH OF COMPLEX AND CONTRAST TRAINING ON PHYSICAL PARAMETERS AMONG SPORTSMEN - Dr.S.Mohanasundaram, Dr.A.Sridharan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Abstract The aims of this experimental analysis were to examine the effects of two different strength and power training. (Complex: CMX and Contrast: CNT training) lower body strength is assigned with repetition maximum (1RM). CMX is one of the most advanced forms of sports training; It has intense strength exercise followed by a plyometric exercise. CNT is the back to back combination training it includes resistance and plyometric exercises. To achieve these study 45 men physical education students were selected as subjects from selvam College of physical education, India. This consists of three equal groups (N=15). Group 1 treated as CMX, Group 2 treated as CNT and Group 3 treated as CG. The subjects were tested on selected criterion variables viz agility and vertical jump. The duration of training was 12 weeks and the level of significance 0.05 was fixed. The Calculated data of before-test and after- test were tool by using analysis of covariance. The results shows that the complex training showed better improvement on explosive power and contrast training showed better improvement on agility. It is concluded that complex training and contrast training is advantageous training for physical education students and sportsmen.